Meta Analysis: Impact of Debt - Equity Swap on Equity - Suryana, Alvian Jihad; Urohman, Taufiq; Hwihanus; Ratnawati, Tri (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Financial difficulties experienced by companies can be caused by management errors, intense competition, market changes, or sluggish economic conditions. This resulted in the company having to restructure its debt to avoid bankruptcy. One way that companies can do this is to carry out a debt-equity swap. We analyze the impact of debt-equity swaps on equity using a meta-analysis method that compares the results of previous studies. The conclusion from this research is that debt- equity swaps can have different impacts. In the short term, debt-equity swaps have a positive impact on equity by reducing the risk of bankruptcy and increasing the company’s cash flow, but also have the potential to reduce equity if carried out when share prices are lower than normal prices. Carrying out massive debt-equity swaps tends to have a negative impact on equity.